(3GdJegjO hGdHjGf aj aVd GdTgjO YKeGfs - (3GHf HcQ , eMeO Hf jMji Hf eMeO Hf jMji Hf CMeO Hf eMeO Hf HcQ GdCTYQj GdeGdcj, CHh YHO Gddg,J (B741 (3g` s
(3ChdgG (B:s
(3CeG HYO , agPG cJGH GPcQ ajg eUQY GdEeGe GdTgjO Pi GdfhQjf YKeGf GHf YaGf ,hCMhGdg , hHYV SjQJg s
(3BNQgG (B:s
(3haQZ ef LeYg hJCdjag eMeO Hf jMji hPdc ai jhe GdKdGKGA , NGeS YTQ Pi GdbYOI ,ef SfI JSY hJSYjf hSJeGFI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B138 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B110s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B259 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B371 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B124 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN e (B23) s
Keywords: (3GdJGQjNs